A Randomized Trial of Soft Multifocal Contact Lenses for Myopia Control: Baseline Data and Methods. Issue 9 (September 2017) - Walline, Jeffrey J.; Gaume Giannoni, Amber; Sinnott, Loraine T.; Chandler, Moriah A.; Huang, Juan; Mutti, Donald O.; Jones-Jordan, Lisa A.; Berntsen, David A.
Abstract : SIGNIFICANCE: The Bifocal Lenses In Nearsighted Kids (BLINK) study is the first soft multifocal contact lens myopia control study to compare add powers and measure peripheral refractive error in the vertical meridian, so it will provide important information about the potential mechanism of myopia control. PURPOSE: The BLINK study is a National Eye Institute–sponsored, double-masked, randomized clinical trial to investigate the effects of soft multifocal contact lenses on myopia progression. This article describes the subjects' baseline characteristics and study methods. METHODS: Subjects were 7 to 11 years old, had −0.75 to −5.00 spherical component and less than 1.00 diopter (D) astigmatism, and had 20/25 or better logMAR distance visual acuity with manifest refraction in each eye and with +2.50-D add soft bifocal contact lenses on both eyes. Children were randomly assigned to wear Biofinity single-vision, Biofinity Multifocal "D" with a +1.50-D add power, or Biofinity Multifocal "D" with a +2.50-D add power contact lenses. RESULTS: We examined 443 subjects at the baseline visits, and 294 (66.4%) subjects were enrolled. Of the enrolled subjects, 177 (60.2%) were female, and 200 (68%) were white. The mean (± SD) age was 10.3 ± 1.2 years, and 117 (39.8%) of the eligible subjects were younger than 10 years. The mean spherical equivalent refractive error, measured by cycloplegic autorefraction was −2.39 ± 1.00 D. The best-corrected binocular logMAR visual acuity with glasses was +0.01 ± 0.06 (20/21) at distance and −0.03 ± 0.08 (20/18) at near. CONCLUSIONS: The BLINK study subjects are similar to patients who would routinely be eligible for myopia control in practice, so the results will provide clinical information about soft bifocal contact lens myopia control as well as information about the mechanism of the treatment effect, if one occurs.